2020
DOI: 10.20344/amp.13970
|View full text |Cite
|
Sign up to set email alerts
|

Will Virtual Teaching Continue After the COVID-19 Pandemic?

Abstract: N/a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Upon review of the current literature, it is evident that medical students have a strong passion and determination to learn during the pandemic. Articles written by Sandhu et al [21] and Marques du Silva [31] demonstrated increased class attendance at webinars and positive student feedback of web-based extracurricular lectures. Guadix et al [10] conducted a survey to understand what medical students with an interest in neurosurgery desired from virtual teaching.…”
Section: Principal Strengths Of Virtual Teachingmentioning
confidence: 97%
“…Upon review of the current literature, it is evident that medical students have a strong passion and determination to learn during the pandemic. Articles written by Sandhu et al [21] and Marques du Silva [31] demonstrated increased class attendance at webinars and positive student feedback of web-based extracurricular lectures. Guadix et al [10] conducted a survey to understand what medical students with an interest in neurosurgery desired from virtual teaching.…”
Section: Principal Strengths Of Virtual Teachingmentioning
confidence: 97%
“…The teacher has not only to transmit the concepts, but has also to foster a learning environment in which the concepts explained are also easily learned [45]. Finally, many teachers have first-hand experience of new technologies and are aware of their utility for approaching certain aspects that are often overlooked in traditional teaching, such as creativity and a critical spirit, so they will be very likely, in the future, to incorporate these tools more often in their classes [46]. In short, these experiences can be used in all fields to improve the quality of their teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Across the world, many governments closed educational institutes in an attempt to curb the spread of pandemic. [ 1 ] Educators across countries were put to the task of virtually teaching dentistry, a course that was designed to be taught face to face and which inherently comprises of developing clinical skills. The pandemic led to an abrupt transition from traditional to virtual classrooms.…”
mentioning
confidence: 99%
“…The pandemic led to an abrupt transition from traditional to virtual classrooms. [ 1 2 ] However, the switch to virtual teaching and learning posed challenges to the educators and the students, especially in developing countries. [ 3 ] The availability of internet facilities was a primary challenge, while the development of skills and understanding of available technology were among the others.…”
mentioning
confidence: 99%